Enhancing Students’ Learning Interest and IPAS Achieve-ment through the Find Someone Who Cooperative Learning Model in Elementary Education - Irmawati Irmawati; Syarifuddin Syarifuddin; Hartini Hartini (International Journal of Humanities and Social Sciences Reviews, 2025)
This study aims to describe the implementation of the Find Someone Who cooperative learning model in increasing fifth-grade students' learning interest in science. The implementation of this model provides an active and enjoyable learning experience through questioning, movement, and discussion activities that enable students to engage in meaningful social interactions. This involvement makes students more enthusiastic about participating in learning and helps them understand concepts better. In addition, the Find Someone Who model encourages collaborative knowledge construction, so students can build conceptual understanding through cooperation and communication. Increasing student interest and participation is one of the important factors that encourages improving the quality of the science learning process in the classroom. This study examines the contribution of the Find Someone Who cooperative learning model to improving fifth-grade students' interest and learning outcomes in science. The results showed an increase in learning completion from 54% in cycle I to 92% in cycle II, which was influenced by collaborative activities that helped students build a more structured understanding of concepts. Through social interaction, information exchange, and cooperation during learning, students were able to strengthen their understanding and develop communication skills. Although its implementation requires good time management and clear instructions, this model still has a positive influence when applied in a targeted and consistent manner. These findings indicate that collaborative learning through the Find Someone Who approach can enrich the science learning process in elementary schools.